The Theme of Displacement in Contemporary Art - John POTTS (E-REA)
This essay considers images and ideas of displacement in recent works of art. The theme of displacement is examined in the context of the globalist aspect of contemporary art, itself a reflection of globalisation. Influential theoretical texts informing curatorial practice and the discourse of contemporary art theory are discussed, including the writings of Girogio Agamben, Nicolas Bourriaud and Rex Butler. The theme of displacement in contemporary art is analysed with regard to the work of many artists, including Francis Alÿs, Bill Fontana, Allan Sekula, Chen Chieh-jen, Ai Wei Wei, Rosemary Laing, Mike Parr, Santiago Sierra, Rebecca Belmore and Tracey Moffatt.